Identification of Antibiotic-Producing Isolates from the Soil of Pesantren Darul Aman Gombara, Makassar - Fhahri Mubarak; Wahyu Hendrarti; Hamdayani Lance Abidin; Arfan Abu Bakar (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
One source of antibiotics-producing microorganisms that are now widely used as a treatment for infections comes from the soil. Soil is an excellent medium for the growth and development of various microorganisms. The search for new antibiotics is currently urgently needed, because their use is not following the instructions, causing disease resistance. This study aims to get antimicrobial-producing microbial isolates that can inhibit the test microbes and identify the type of isolates. The first stage of microbial isolation was the dilution of the soil sample from 10-1 to 10-5 using the method of pouring on Nutrient Agar (NA) and Potato Dextrose Agar (PDA) medium. It carried further testing of antimicrobial activity against several test microbes out. The results of the isolation got 4 isolates of bacteria and 4 isolates of fungi with different identification of each isolate. In the test microbe, Escherichia coli isolates that gave activity were isolates IB1, IB2, IB3. In the Staphylococcus aureus test bacteria, the isolate that produces activity is the isolate IB1, IB2, IB3, IB4, IJ2, Meanwhile, for the test fungus Candida albicans was inhibited by isolates IB1, IJ1, IJ2, IJ3 and IJ4.